Morphological Analysis of Fashion Terms in Vogue’s Website Article - Silalahi, Elisa Debora (Institut Agama Islam Negeri Ponorogo, 2024)
Language has evolved into a powerful depiction of the changes and evolutions occurring in the continually expanding fashion business. It is particularly identifiable in the vocabulary employed in the fashion industry, which is getting increasingly sophisticated in both structure and usage. This research aims to examine the word formation process of fashion terminology. As qualitative research, this research utilizes seven articles taken from the Vogue website published between the 5th and 7th of May related to the Coronation of King Charles III as data sources. Applying the word formation process proposed by Yule (2020) reveals that four types of word formation processes occur in 22 fashion terminology: derivation, compounding, borrowing, and multiple processes. The dominance of compounding highlights that fashion items undergo modifications in their type based on the compound terms' heads. Furthermore, the process with the second-highest number is derivation, which was created to meet a constant demand to represent new concepts in fashion terminology. Furthermore, the borrowing process reveals that all loanwords originated in French. It is supported by the fact that Paris, the French capital, is renowned as Europe's fashion center. Furthermore, the last process in this research is multiple processes, which involve two processes: borrowing and compounding.